The political and social repercussions of terrorism on young people in Iraq after 2003 (قضايا سياسية, 2023)
Psychological and social studies have proven that young people are more emotional and interactive in society, and more willing to be drawn after the temptations of life, deviation, mental disorders and being affected by new trends and unstudied imitation. These studies have confirmed that there is a dialectical correlation between the increase of deviation among young people and and the nature of the social, economic and cultural structure of the society, as it can be noticed in industrial advanced societies, for instance. And on the contrary, we note the decline of this phenomenon in societies known as (conservative) in which religious principles, values, morals and virtue prevail, such as in the Islamic societies. Young people represent a high proportion of the population in Arab and Islamic societies and developing countries, including Iraq. Therefore, we find that the nature of the political and social in Iraq after 2003 and the accompanying security disturbances resulted from the American occupation and the presence of terrorist groups that tried to influence the thought of young people and recruit them on their side. Yet, Iraqi society as whole, represented in the political, religious and social institutions have played a significant role in confronting these ideas and protecting young people from them.